Physical activity in Sami and non-Sami populations in rural Northern Norway, the SAMINOR 2 Clinical Survey - Borch, Kristin Benjaminsen; Eliassen, Bent Martin; Melhus, Marita; Damsgård, Elin; Broderstad, Ann Ragnhild (BMC Public Health, 2021)
Background - The Sami people is an indigenous minority population living in the northern parts of Norway and mainly in rural areas. We lack data of contemporary levels of physical activity (PA) in rural regions of Northern Norway and in the Sami population in particular. We aimed to describe the PA levels and investigate whether PA levels differs between Sami and non-Sami and between coastal and inland areas. Methods - We used data from the second survey of the Population-based Study on Health and Living Conditions in Regions with Sami and Norwegian Populations – the SAMINOR 2 Clinical Survey (2012–2014) that includes the adult population in 10 municipalities in the counties Troms, Finnmark and Nordland. Participants self-reported on PA, ethnicity and modifiable lifestyle factors. Twelve thousand four hundred fifty-five individuals were invited with a response rate of 48.2% (n = 6004 participants). We tested differences using chi-square tests, two sample t-tests and linear regression models. Results - Among 5628 participants, 41.1 and 40.9% of men and women, respectively, were defined as Sami. We found no ethnic differences in PA in men overall. However, Sami men living in Tana, and Nesseby reported higher PA compared to non-Sami men in the same area. For Sami women there was overall lower PA levels compared to non-Sami women, especially pronounced in Kautokeino/ Karasjok. Conclusion - This study showed small differences in PA levels between Sami and non-Sami men. Sami women had lower PA levels compared to their non-Sami counterparts. It is important to identify whether there are differences in various ethnic populations, together with other predictors for PA in future planning of public health interventions.